The prognostic implications of comorbidities in septic arthritis - Khudair, Aiman; Khudair, Ahmed; Butler, Alexandra E. (Frontiers in Medicine, 2025)
Septic arthritis (SA) is an orthopedic emergency characterized by joint inflammation secondary to infectious etiologies, most commonly Staphylococcus aureus. The prompt recognition of SA is crucial due to its significant morbidity and mortality. Fever, along with a swollen, painful joint and limited range of motion, are typical manifestations; however, presentations can vary. The incidence of SA in adult populations is rising, accompanied by unfavorable mortality rates. This trend is further exacerbated by comorbid conditions that substantially influence outcomes. Among the literature, diabetes mellitus (DM), rheumatoid arthritis (RA), and chronic kidney disease (CKD) have emerged as key prognostic factors in SA. DM exacerbates the severity of SA through impairment of polymorphonuclear function, ultimately leading to increased susceptibility to infection and a higher risk of acquiring infection from atypical pathogens. CKD causes uremia-induced immune dysfunction leading to an immunocompromised state as well as repeated vascular access increasing infection susceptibility, leading to increased mortality. Patients with RA harbor an elevated risk of SA, attributed to immune dysregulation, immunosuppressive therapy, and diagnostic challenges. Additionally, these comorbidities can complicate the surgical management of SA and increase the likelihood of treatment failure. Therefore, given the rising burden of comorbid conditions worldwide and their impact on SA prognosis, healthcare professionals should remain vigilant when managing these factors. A holistic, multidisciplinary approach to management is vital to ensure that SA patients with these certain comorbid conditions experience fewer complications and improved survival. This mini-review aims to highlight the key comorbid conditions that impact the prognosis of SA patients.